Identifikasi Potensi Wilayah Nagari Anduring Kecamatan 2x11 Kayu Tanam Kabupaten Padang Pariaman - Suryanto, Fitri Adi; Adil, Sita Darma; S, Syaiful; O, Osronita; J, Jamilah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Anduring Village or Nagari is one of the villages located in the 2X11 Kayu Tanam District, Padang Pariaman Regency which has an area of 133.85 km². Nagari Anduring has seven smaller administrative areas or korong, namely Korong Rimbo Kalam, Korong Asam Pulau, Korong Kampuang Tangah, Korong Lubuk Napa, Korong Sipisang Sipinang, Korong Lubuk Aua, and Korong Balah Aia. Nagari Anduring has not brought in many local tourists on a regular basis, this is due to many contributing factors such as inadequate infrastructure and more than half of the area is a natural reserve forest with a slope of 15% to 45%. Nevertheless, Nagari Anduring has the potential for tourist attractions with attractive natural scenery such as waterfalls, rivers and from the agricultural sector. The purpose of this research is to identify and map the tourism potential in Nagari Anduring so that later it is expected to have a positive impact on the economy of the Nagari Anduring community.